Energy flux across multitrophic levels drives ecosystem multifunctionality: Evidence from nematode food webs. (June 2022) - Wan, Bingbing; Liu, Ting; Gong, Xin; Zhang, Yu; Li, Chongjun; Chen, Xiaoyun; Hu, Feng; Griffiths, Bryan S.; Liu, Manqiang
Abstract: Energy flux in food webs, i.e., energy consumption by different trophic groups and describing their energetic structure, has been proposed as a powerful tool to understand the relationships between biodiversity and multiple ecosystem functions (ecosystem multifunctionality). Here we examined how different fertilization regimes affected the energy flux across multitrophic levels of soil nematodes in the paddy rice and upland maize fields. We considered 13 ecosystem functions of four ecological processes related to plant productivity, nutrient cycling processes and drivers, and functional stability, which are central to energy and nutrient flow across trophic levels. To confirm whether multitrophic flux would underpin the relationships between biodiversity and multifunctionality, we compared energy flux with other approaches including taxonomic diversity, functional diversity and community composition. Results showed that organic fertilizer supported 33–340% greater multitrophic energy flux of soil nematode community and enhanced 41–264% of ecosystem multifunctionality in both fields compared with mineral fertilizer treatments. Organic fertilization enhanced ecosystem multifunctionality by favoring energy flux in multitrophic levels of soil nematodes, while fertilization-mediated changes in other facets of biodiversity were less related to multifunctionality. Our study provides empirical evidence that energy flux within food webs can be used to understand the impacts of environmental change drivers on ecosystem multifunctionality. Highlights: Organic fertilization increased ecosystem multifunctionality. Energy flux of soil nematodes was positively related to multifunctionality. Energy flux underpinned the link between biodiversity and multifunctionality.